Disseminated Nocardiosis in a Patient with Chronic Granulomatous Disease: A Case Report - Rahman, M Ekhlasur; Rahman, AKM Matiur; Rahman, Mowshumi; Ali, Md Ramzan; Chowdhury, Abu Sayeed; Shams, Nusrat; Haque, Jalaluddin Ashruaful (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v35i2.10380 Bangladesh J Child Health 2011; Vol 35 (2): 68-70